Pengaruh Pelatihan Kerja, Pengembangan Karir, Dan Kepuasan Kerja Terhadap Kinerja Pegawai Melalui Motivasi Kerja Sebagai Variabel Intervening Pada Dinas Peternakan Dan Kesehatan Hewan Provinsi Sumatera Barat - Prima senja ananda; Vivi Nila Sari; Resyelly viona (Jurnal Ekonomi dan Bisnis Digital, 2026)
The purpose of this study was to examine the effect of job training, career development, and job satisfaction on employee performance through work motivation as an intervening variable at the Livestock and Animal Health Service Office of West Sumatra Province. This study employed a quantitative research method using a Structural Equation Modeling (SEM) approach with SmartPLS 3.0 as the analysis tool. The population and sample of this study consisted of all employees of the Livestock and Animal Health Service Office of West Sumatra Province. Data were collected through questionnaires and analyzed to test the proposed research hypotheses. The results of the study indicated that job training, career development, and job satisfaction have a positive and significant effect on work motivation. Furthermore, job training, career development, job satisfaction, and work motivation have a positive and significant effect on employee performance. These findings indicate that work motivation plays an important role in improving employee performance. In addition, work motivation is proven to mediate the effect of job training on employee performance, as well as mediate the effect of career development and job satisfaction on employee performance at the Livestock and Animal Health Service Office of West Sumatra Province.